2008
DOI: 10.3233/jad-2008-15105
|View full text |Cite
|
Sign up to set email alerts
|

SNPs in Neurotrophin System Genes and Alzheimer's Disease in an Italian Population

Abstract: Increasing evidence suggests a role for nerve growth factor (NGFB), brain-derived neurotrophic factor (BDNF), and their receptors, nerve growth factor receptor (NGFR), and neurotrophin tyrosine kinase receptors 1 and 2 (NTRK1 and NTRK2), in Alzheimer's disease (AD). However, genetic association between the neurotrophin system genes and AD has been poorly investigated. We genotyped 21 single nucleotide polymorphisms (SNPs) within these genes in a population of Italian AD patients and healthy controls. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 47 publications
4
59
3
Order By: Relevance
“…Heterozygous carriers of the T-allele tend to have a higher risk of developing AD than non-carriers (36). There have been a total of four significant results (13,(17)(18)(19)) and 14 non-significant results (28)(29)(30)(31)(34)(35)(36)(37)40,41,(43)(44)(45) among the previous association studies between the BDNF C270T polymorphism and AD. In the present meta-analysis, the BDNF C270T polymorphism was found to increase the risk of AD by 88% in Asians under the dominant model.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Heterozygous carriers of the T-allele tend to have a higher risk of developing AD than non-carriers (36). There have been a total of four significant results (13,(17)(18)(19)) and 14 non-significant results (28)(29)(30)(31)(34)(35)(36)(37)40,41,(43)(44)(45) among the previous association studies between the BDNF C270T polymorphism and AD. In the present meta-analysis, the BDNF C270T polymorphism was found to increase the risk of AD by 88% in Asians under the dominant model.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have reported five positive results (12-16) and 21 negative results (19,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) between the BDNF Val66Met polymorphism and AD. In the present meta-analysis, no significant association was found between BDNF Val66Met and AD (P>0.05, Table II).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…89,90 Finally, p75 NTR has also been shown to physically and functionally interact with APP, 91 and a direct genetic link between p75 NTR and AD has been suggested. 92 …”
Section: P75 Ntr As a Putative Trigger Of Neuronal Tetraploidy In Admentioning
confidence: 99%
“…Detailed characteristics of all eligible studies included in meta-analysis are reported in Table 1. One overall study was conducted on BDNF 196GA polymorphism and 3 ethnicity specific studies were conducted, that includes 8 studies on American populations [30][31][32][33][34][35][36], 11 studies on Asian populations [37][38][39][40][41][42][43][44][45][46][47] and 12 studies on European populations [35,[48][49][50][51][52][53][54][55][56][57][58]. Moreover, one overall study was also conducted on BDNF 270CT polymorphism and 3 ethnicity specific studies were also possible, that includes 5 studies on American populations [30,31,33,34,59], 7 studies on Asian populations [37,39,41,42,44,46,60] and 7 studies on European populations [48,49,52,…”
Section: Eligible Studies Included In the Meta-analysismentioning
confidence: 99%